KAPABILITAS DYNAMIC GOVERNANCE DALAM OPTIMALISASI PENGELOLAAN LAHAN TERBUKA HIJAU DI KOTA MAKASSAR - Tahir, Muchlas M; Nahrudin, Zulfan (Departemen Ilmu Pemerintahan FISIP UNPAD, 2017)
This study aims to determine the development of Dynamic Governance Capabilities in optimizing the management of green open land in the city Makassar.Metode This study used a qualitative approach through the instrument interview, observation and documentation. The process of data analysis including data collection, data reduction, data presentation, and conclusion. The results showed the vertical system in the optimization of green open land needs to be supported by the active participation of the community by contributing as much as 10% of their land to green open land in addition to the boost in the form of pemerdayaan green community as a form of community participation in the optimization of open land needs to be strengthened by the municipality at the same time show the need to demonstrate the utilization of spaces awakened by way of planting on the roofs and walls of buildings in addition to the strategy in terms of policies can be reached by encouraging the preparation and adoption of Local Regulations related to the RTH is part of our capability Dynamic Governance includes thinking ahead (thinking ahead), thinking again (thinking again), and cross-border thinking (thinking across), which focuses on optimizing the management of green space produces a series of adjustments to the program as program Lorong garden (Loose) which can contribute to the optimization of green space in the city of Makassar.